The Affixation Process Pattern of the Batak Pakpak Dairi Language - Rahel Theresia Rodame Situmorang; Tifany; Arjuna Junifer Siregar; Dion Nardi Pangaribuan; Erikson Saragih; Asriaty R. Purba (Raja Zulkarnain Education Foundation, 2025)
Language is not only a means of communication, but also a reflection of the identity and culture of a society; Through this research on Pakpak Dairi language affixations, researchers invite readers to explore the unique structure and function, the meaning behind each affix which enriches the Batak linguistic heritage. This research aims to describe the types, functions and meaning of affixation. Affixation in the Pakpak Dairi language is the process of a word experiencing affixes, the types of affixes in the Pakpak Dairi language are divided into four groups, namely: Prefixes (i-, me, mer, pe, per, se, and ter) Infixes (-in-, and –um-), Suffixes – en, -i, -ken,), Confixes (ke-en, mersi-en). The function of Pakpak Dairi language affixations is where the four affixations change form into passive verbs and active verbs and the meaning of affixations is where the data from the four affixations are interpreted into a sentence. The method used in this research is a literature study method. Based on the results of data analysis, it can be found that there are 52 affixation types, 29 words for prefix affixation functions, 10 words for suffixes, 8 words for infixes, and 5 words for confixes.